Aplikasi al-‘Urf sebagai Metode Istinbath Hukum Ekonomi Kontemporer dalam Kajian Uang Elektronik - Rijal, Akmalur; Ghozali, Muhammad Lathoif; Yasid, Abu (Kartika: Jurnal Studi Keislaman, 2026)
The rapid development of financial technology has brought electronic money (e-money) into modern payment systems as a new phenomenon. However, the absence of explicit textual provisions in classical Islamic jurisprudence creates a legal vacuum that requires methodological resolution. This study employs a qualitative approach using a library research methodology, analyzing primary and secondary sources on the al-'urf doctrine and electronic money regulations in Indonesia. The analysis reveals that electronic money fulfills four conditions required for al-'urf to serve as a valid legal source: (1) it has been practiced continuously and widely accepted by the majority of Indonesian society; (2) the practice preceded formal legal determination; (3) it is transparent and free from ambiguity; (4) it does not contradict Islamic sacred texts (nash syara'). DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017 on sharia-compliant electronic money confirms this position by grounding its legal reasoning in the fiqh maxim that customary practice carries the same legal weight as explicit sharia provisions. Electronic money is permissible under Islamic law when conducted through sharia-compliant platforms, as established by the al-'urf methodological framework. This finding implies that al-'urf remains a dynamic and applicable legal instrument for addressing contemporary economic innovations not explicitly covered by classical fiqh texts.